Corpo-archivio: mappatura di una nozione tra incorporazione e pratica coreografica - Susanne Franco (Ricerche di S/Confine, 2019)
The text proposes a historical-theoretical exploration of the concept of “body-archive” that has proved to be central both for the recent trends of dance historiography and for the artists who increasingly dialogue with the past through their reenactments of choreographic works or dance traditions. The metaphor of the body-archive refers to the idea that the materiality of the body can be understood as a set of documents capable of suggesting meanings beyond the physical dimension and of preserving traces of knowledge as remote as it in constant transformation. Whether it is the embodied memory of the dancer, the visual, emotional and kinaesthetic memory of the audience, or techological divices to record dance, to write about dance and to dance necessarily requires a specific concept of archive. The many theories of the body as an archive advanced by scholars and artists are substantiating new theoretical and practical approaches to the history of dance, and are helping to deconstruct, thanks also to the contributions of studies on memory, narratives and genealogies resulting from more traditional methodological and theoretical approaches.